Environmental and social responsibility management in international entrepreneurship in EU countries - Sribna, Yevheniia; Shmatko, Nataliia; Kustrich, Liliya; Parhomenko, Lyudmila; Neboha, Tetiana; Lytvynenko, Alina; Lytvynenko, Elena (My University, 2023)
The research developed a specific mechanism of analysis that connected the fundamental developments of the classics of economics with the real economic processes of today. This approach made it possible to create more flexible evaluation tools as well as to calculate the level of social security based on statistical data and, as a result, to understand and explain the main trends in social security. An analysis of the fundamental foundations of the functioning of the economic system was carried out, and the main factors in the formation of the country's economic income were indicated. It is explained how these factors operate in the modern global business environment and lead to an increase in problems in the social sphere. The necessary and permissible level of investment to maintain social balance in society was noted, with an indicator of 4% of GDP. It has been proven that Iceland has guaranteed social development at a level of 271%, which is the highest indicator among European countries. Statistical data for EU countries were analysed, and the calculation of indicators made it possible to assess the state of social assistance in geographical regions of Europe.
Keywords: economy; finance; international entrepreneurship; management; ecology